Competition and gender: Time's up on essentialist knowledge production. Issue 1 (February 2021) - Mavin, Sharon; Yusupova, Marina
This article is an intervention in current trends of thinking about competition and gender in essentialist and stereotypical ways. Such thinking has produced numerous comparative studies measuring competitiveness of women and men; 'proving' men as competitive and women as non-competitive. Based on experiments and written questionnaires, these studies reduce gender to perceived biological sex and treat competition as a 'self-evident', static and easily measurable phenomenon. To contribute new understandings and learning, we surface five fallacies of this comparative research, explaining why the approach is misleading, inequitable and socially harmful. Drawing upon gender as a social construction and women leaders' narratives, we offer a blueprint for democratising knowledge production. We write differently, choosing not to provide a 'balanced' view of the field and construct competition as a processual, complex and contextually specific phenomenon with underlying gender dynamics, rather than a discrete, observable and fixed in time event. The article provides learning: for leaders and managers to resist automatic categorisation on the basis of perceived biological sex; for management educators to challenge the ways that leadership and management are traditionally taught; and, for executive coaches to support changes in practice, by embracing complexity of the contemporary contexts in which leaders operate.